Reproducing American Sign Language sentences: cognitive scaffolding in working memory - Supalla, Ted; Hauser, Peter C.; Bavelier, Daphne (Frontiers in Psychology, 2014)
The American Sign Language Sentence Reproduction Test (ASL-SRT) requires the precise reproduction of a series of ASL sentences increasing in complexity and length. Error analyses of such tasks provides insight into working memory and scaffolding processes. Data was collected from three groups expected to differ in fluency: deaf children, deaf adults and hearing adults, all users of ASL. Quantitative (correct/incorrect recall) and qualitative error analyses were performed. Percent correct on the reproduction task supports its sensitivity to fluency as test performance clearly differed across the three groups studied. A linguistic analysis of errors further documented differing strategies and bias across groups. Subjects' recall projected the affordance and constraints of deep linguistic representations to differing degrees, with subjects resorting to alternate processing strategies when they failed to recall the sentence correctly. A qualitative error analysis allows us to capture generalizations about the relationship between error pattern and the cognitive scaffolding, which governs the sentence reproduction process. Highly fluent signers and less-fluent signers share common chokepoints on particular words in sentences. However, they diverge in heuristic strategy. Fluent signers, when they make an error, tend to preserve semantic details while altering morpho-syntactic domains. They produce syntactically correct sentences with equivalent meaning to the to-be-reproduced one, but these are not verbatim reproductions of the original sentence. In contrast, less-fluent signers tend to use a more linear strategy, preserving lexical status and word ordering while omitting local inflections, and occasionally resorting to visuo-motoric imitation. Thus, whereas fluent signers readily use top-down scaffolding in their working memory, less fluent signers fail to do so. Implications for current models of working memory across spoken and signed modalities are considered.